Nuclear medicine and molecular imaging - Ziessman, Harvey A.; O'Malley, Janis P. (Philadelphia, PA : Elsevier Mosby, 2021)
Prepare for examinations and enhance your clinical practice with this best-selling Requisites title! Now in its 5th Edition, this outstanding volume in the popular Requisites series thoroughly covers the fast-changing field of nuclear medicine and molecular imaging. Ideal for residency, clinical rotations, and board review, this compact and authoritative volume covers the conceptual, factual, and interpretive information you need to know for success on exams and in clinical practice. New to this edition : more content on molecular imaging and the latest advances in clinical applications, including positron emission tomography (PET), SPECT/CT, PET/CT, and PET/MRI hybrid imaging ; inclusion of newly approved tracers such as Ga68 DOTA, F-18 amyloid, and F-18 PSMA ; expanded and integrated content on physics and non-interpretive aspects, including regulatory issues, radiation safety, and quality control ; up-to-date applications of nuclear medicine in the endocrine, skeletal, hepatobiliary, genitourinary, pulmonary, gastrointestinal, central nervous, and cardiac systems, as well as PET applications for oncology. In the outstanding Requisites tradition, the 5th Edition also : summarizes key information with numerous outlines, tables, pearls, pitfalls, and frequently asked questions ; focuses on essentials to pass the certifying board exam and ensure accurate diagnoses in clinical practice ; helps you clearly visualize the findings you're likely to see in practice and on exams with nearly 200 full-color images.--taken from back cover.
Part 1. Basic principles -- Chapter 1. Radioactivity and radionuclides -- Chapter 2. Radiation detection & ancillary instrumentation -- Chapter 3. Single-photon emission computed tomography, positron emission tomography, and hybrid imaging -- Chapter 4. Radiopharmaceuticals -- Chapter 5. Molecular imaging -- Part 2. Clinical studies -- Chapter 6. The skeletal system -- Chapter 7. The pulmonary system -- Chapter 8. Endocrine system -- Chapter 9. Hepatic, biliary, and splenic scintigraphy -- Chapter 10. Gastrointestinal system -- Chapter 11. Urinary tract -- Chapter 12. Oncology : F-18 fluorodeoxyglucose positron emission tomography -- Chapter 13. Oncology : Beyond fluorodeoxyglucose -- Chapter 14. Central nervous system -- Chapter 15. Inflammation and infection -- Chapter 16. Cardiovascular system -- Chapter 17. Pearls, pitfalls and frequently asked questions -- Appendix 1. Dosimetry -- Appendix 2. The Periodic Table of the Elements -- Index.
Preceded by: Nuclear medicine / Harvey A. Ziessman, Janis P. O'Malley, James H. Thrall. Fourth edition. [2014].
Includes bibliographical references and index.
Keywords: Diagnostic Techniques, Radioisotope; Molecular Imaging; Nuclear Medicine; Radionuclide Imaging; Radiopharmaceuticals